2011
DOI: 10.1158/1078-0432.ccr-10-2915
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Transcriptional Profiling for Predicting Response to Neoadjuvant Chemoradiotherapy in Rectal Adenocarcinoma

Abstract: Purpose: Patients presenting with locally advanced rectal cancer currently receive preoperative radiotherapy with or without chemotherapy. Although pathologic complete response is achieved for approximately 10% to 30% of patients, a proportion of patients derive no benefit from this therapy while being exposed to toxic side effects of treatment. Therefore, there is a strong need to identify patients who are unlikely to benefit from neoadjuvant therapy to help direct them toward alternate and ultimately more su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 43 publications
0
51
0
1
Order By: Relevance
“…Six different studies have previously attempted to identify gene expression signatures capable of predicting response to nCRT in rectal cancer patients using microarrays [12][13][14][15][16][17]. Gene lists for five of these six studies were available for testing on the RNA-Seq data generated for the 25 patients in our cohort (Table 4) The gene signature identified by Gahdimi et al [12] showed the highest accuracy (76%) in our cohort, with 66.7% sensitivity and 81.2% specificity.…”
Section: Validation Of Published Gene Signaturesmentioning
confidence: 91%
See 2 more Smart Citations
“…Six different studies have previously attempted to identify gene expression signatures capable of predicting response to nCRT in rectal cancer patients using microarrays [12][13][14][15][16][17]. Gene lists for five of these six studies were available for testing on the RNA-Seq data generated for the 25 patients in our cohort (Table 4) The gene signature identified by Gahdimi et al [12] showed the highest accuracy (76%) in our cohort, with 66.7% sensitivity and 81.2% specificity.…”
Section: Validation Of Published Gene Signaturesmentioning
confidence: 91%
“…Many studies have attempted to identify a clinically useful and reproducible gene expression signature capable of predicting response to nCRT using microarrays [12][13][14][15][16][17]. Most studies have focused on the identification of predictive signatures to distinguish "good" responders from "bad" responders and were primarily interested in the identification of patients that would benefit the most from nCRT and spare others from the potential toxicity of CRT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the authors not only obtained limited sensitivity and specificity in their cohort, but also failed to confirm the power of previously published predictive classifiers, possibly as a result of the different biological characteristics of the sample sets or of transcription changes that were too small to be detected. 40 However, as highlighted by Watanabe et al, the use of qRT-PCR to construct a prediction model based on expression evaluation of a small number of significant genes selected in microarray studies is more feasible in clinical practice and allows for accurate and reproducible quantification of mRNA obtained from even small amounts of fresh-frozen or paraffin-embedded tissue. 39 …”
Section: Gene Expressionmentioning
confidence: 99%
“…Several studies have attempted to establish a clinically useful gene signature capable of predicting response to nCRT [40][41][42][43]. Even though more than 17 signatures have been reported with nearly 1000 genes, there is minimal overlap between genes in all of these signatures.…”
mentioning
confidence: 99%